What cool fish live in icy Antarctica? - DANISH - Lopez, Isabel; Postlethwait, John; Desvignes, Thomas (University of Oregon Science and Comics Initiative, 2024)
The Southern Ocean that surrounds Antarctica is one of the coldest on earth and hovers freezing temperatures year-round. What fish can live in such a frigid environment? In this short scientific graphic novel, What cool fish live in icy Antarctica? , Isabel Lopez, John Postlethwait and Thomas Desvignes present the history of Antarctica and how it became the icy continent. These glacial conditions prevented most fish species from living there, but one group, the notothenioids, evolved a way to survive and even thrive in the ice-cold Antarctic waters. They diversified from the surface to the dark depths of the ocean, from being just a few centimeters long to extremely large, and in many other surprising ways. And among them, the white-blooded icefishes are also certainly some of the strangest fish on the planet! But today, Antarctica is changing fast, raising concerns about the survival of these unique fish. Click on the image below to read the graphic novel in English. Or scroll further down to read the graphic novel in one of the additional nine languages available! And if you like the graphic novel, share it: On Facebook On X/Twitter On LinkedIn By Email The font used in the graphic novel is OpenDislexic-Alta , a typeface designed against some common symptoms of dyslexia. This comic was created as part of the University of Oregon Science and Comics Initiative . This material is based upon work supported by the Office of Polar Programs at the National Science Foundation under NSF grant number OPP-2232891. Any opinions, findings, and conclusions or recommendations expressed in this material are those of the authors and do not necessarily reflect the views of the National Science Foundation. And our previous short scientific graphic novels are also still publicly available! “ What controls sex development in fish? ” in ten languages! “ A mysterious disease in Antarctic fish ” in five languages!